Negotiating the EU's 2030 Climate and Energy Framework Agendas, Ideas and European Interest Groups - Fitch-Roy, Oscar (Progressive Energy Policy, 2018)
'This book presents complex information in an easy and compelling read. It is splendidly well-researched, and gives a thorough explanation of how plotting and persuasion by the community of interest groups, large corporations, and their lobbyists and campaigners influenced the 2030 framework. This highly valuable insight into the deeper parts of the EU climate and energy policy processes should be read by academics and stakeholders alike.' - Tor Håkon Jackson Inderberg, Senior Research Fellow and European Programme Director, Fridtjof Nansen Institute, Norway In 2014, European heads of state selected new targets for the EU as part of the 2030 climate and energy framework. These targets will guide the ambition and nature of EU policy in this area until 2030 and are likely to have important implications for Europe's transition to a low-carbon economy. This book exposes the role of civil society and business interest groups in setting the policymaking agenda and defining the range of options for the framework. Based on a unique sample of 32 in-depth interviews with Brussels policy elites, this book casts EU interest representation in a new light. In a novel application of the 'multiple streams approach', sequential chapters present the problems faced by policymakers, the range of policy options available to address them and the political constraints within which policy entrepreneurs attempted to attached policies to problems. .